Nimotuzumab plus chemotherapy and immunotherapy as first-line/neoadjuvant therapy for advanced esophageal squamous cell carcinoma - Wang, Qi; Cui, Zhi; Deng, Muhong; Zhang, Guoqing; Jing, Fangfang; Ma, Yue; Pang, Fang; Han, Quanli (Frontiers in Pharmacology, 2025)
BackgroundNimotuzumab has shown promising efficacy in esophageal squamous cell carcinoma (ESCC). However, the efficacy and safety of nimotuzumab plus chemotherapy and immunotherapy as first-line/neoadjuvant therapy for patients with advanced ESCC remain unclear.MethodsWe performed a real world study of patients with advanced ESCC from December 2019 to April 2024. Patients were classified into resectable and unresectable group. Dosing regimen: nimotuzumab (400 mg, Q3W) plus chemotherapy (nab-paclitaxel: 240 mg/m2, paclitaxel liposome: 135–175 mg/m2, platinum: 200–400 mg/m2, Q3W) and immunotherapy (PD-1/PD-L1: 200–240 mg, Q3W). Overall survival (OS) and progression-free survival (PFS) were primary endpoints, objective response rate (ORR), disease control rate (DCR), and safety were secondary endpoints.ResultsTotally 55 patients were included, 15 in resectable group and 40 in unresectable group. The median follow-up was 36.70 months and 34.00 months, respectively. In resectable group, ORR was 100.0%, DCR was 100.0%, R0 resection rate was 100.00%, 1-year OS was 84.00%, 2-year OS was 74.67% with 34.46 months median OS, 1-year PFS was 84.00%, and 2-year PFS was 37.33% with 21.68 months median PFS. In unresectable group, ORR was 70.0%, DCR was 90.0%, 1-year OS was 76.70%, 2-year OS was 51.29% with 28.06 months median OS, 1-year PFS was 56.64%, and 2-year PFS was 31.15% with 14.95 months median PFS. 14 (25.5%) patients developed Grade 3–5 adverse events (AEs) not related to nimotuzumab, no serious AEs or deaths occurred.ConclusionOur treatment combination for advanced ESCC showed a favorable survival profile, and safety was tolerable.